2010
DOI: 10.1002/jms.1847
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐dependent dissociation of benzylpyridinium ions in an ion‐trap mass spectrometer

Abstract: Benzylpyridinium ions, generated via electrospray ionization of dilute solutions of their salts in acetonitrile/water, are probed by collisional activation in an ion-trap mass spectrometer. From the breakdown diagrams obtained, phenomenological appearance energies of the fragment ions are derived. Comparison of the appearance energies with calculated reaction endothermicities shows a reasonably good correlation for this particular class of compounds. In addition, the data indirectly indicate that at threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 66 publications
2
105
0
1
Order By: Relevance
“…It is noteworthy that the ion at m/z 91 here should be benzyl cation. Previous theoretical studies suggested that conversion of the benzyl cation to the tropylium ion must surmount a significant energy barrier (65.0 kcal mol −1 [30], 67.8 kcal mol −1 [31]), so this process was usually not considered to occur in ESI mass spectrometry [32,33] though rare exceptions had been reported in the fragmentations of some benzylpyridinums [34][35][36]. For the occurrence of intra-complex reaction, INC-1 should have suitable amount of internal energy, which is enough for further reaction between the ion and the neutral species but not enough for direct separation.…”
Section: Fragmentation Of Protonated Nn′-dibenzylpiperazinementioning
confidence: 99%
“…It is noteworthy that the ion at m/z 91 here should be benzyl cation. Previous theoretical studies suggested that conversion of the benzyl cation to the tropylium ion must surmount a significant energy barrier (65.0 kcal mol −1 [30], 67.8 kcal mol −1 [31]), so this process was usually not considered to occur in ESI mass spectrometry [32,33] though rare exceptions had been reported in the fragmentations of some benzylpyridinums [34][35][36]. For the occurrence of intra-complex reaction, INC-1 should have suitable amount of internal energy, which is enough for further reaction between the ion and the neutral species but not enough for direct separation.…”
Section: Fragmentation Of Protonated Nn′-dibenzylpiperazinementioning
confidence: 99%
“…In electrospray ionization mass spectrometry (ESI-MS), fragmentation of benzylated cations prefers to generate benzyl cations [7,8,[20][21][22][23][24][25][26][27][28][29][30], though a few exceptions have been reported that tropylium ion can be co-produced in the fragmentation of benzylpyridinium ions [18,31,32]. Besides the formation of benzyl cations, other interesting ions resulting from hydride transfer [24,25] or electrophilic aromatic substitution reactions [20][21][22] via the nonconventional ion/neutral complex (INC) can also be generated in the dissociation of benzylated cations.…”
Section: Introductionmentioning
confidence: 99%
“…The precursor ion dissociates into a fragment ion (benzylium ion A or tropylium ion B) and a neutral pyridine molecule [18,26,27]. In order to derive ion internal energies from the measurements of ion survival yields, the dissociation energies for each BzPy ion are required.…”
Section: Dissociation Energy Calculationsmentioning
confidence: 99%
“…Fragmentation by bond cleavage between the benzyl and pyridinium moieties occurs for all substituted BzPy ions. Thus, a typical mass spectrum for a substituted BzPy ion contains two peaks, one for the precursor ion and one for the main fragment ion due to the loss of pyridine [18]. The corresponding ion dissociation energetics of BzPy ions have been mainly obtained by electronic structure calculations of varying quality and used as a reference to estimate the internal energy of conventional ionization methods, such as MALDI [19,20], ESI [16,21], desorption electrospray ionization (DESI) [22], direct analysis in real time (DART) [23], and silicon nanoparticle-assisted laser desorption/ionization (SPALDI) [24].…”
Section: Introductionmentioning
confidence: 99%